A comparison of the diet and fine‐scale distribution of sympatric Tibetan and red foxes in Qinghai, PR China. Issue 6 (1st December 2014) - Tsukada, Hideharu; Li, Wei; Duo, Hong; Guo, Zhihong; Fu, Yong; Peng, Mao; Shen, Xiuying; Jing, Jianwu; Yuan, Aishan; Ni, Ma; He, Shengde; Huang, Fuqiang; et al.
Abstract : We compared the diet and the spatial distribution of the Tibetan fox Vulpes ferrilata and the red fox Vulpes vulpes in the Tibetan plateau, to elucidate mechanisms of coexistence for these two sympatric canids and to clarify their roles as definitive hosts for zoonotic Echinococcus parasites. Diet and fine‐scale distribution patterns were assessed by fecal DNA analysis. A total of 45 fecal samples (15 belonging to Tibetan fox, 30 belonging to red fox were collected from 15 sites into three of which contained only Tibetan fox feces, six only red fox feces, and six contained feces of both species. The abundance of pika burrows, a key prey item for both species, did not differ among the sites. Food composition analysis, estimated using a point‐frame method, revealed slight but insignificant differences between the two species. Tibetan foxes consumed primarily mammals, whereas red foxes consumed primarily insects. The dietary range of the Tibetan fox was narrower than that of the red fox but there was little dietary overlap between the two species. These findings suggest that the weak partitioning of food resources between Tibetan and red foxes can facilitate their coexistence even within the same habitat where they share the same key prey items, i.e. small mammals such as pikas. These dietary differences between the two fox species also suggest that the Tibetan fox is a more important definitive host for Echinococcus on the Tibetan plateau than is the red fox.